Durability method on corrosion fatigue performance of AH 32 steel (Fracture and Structural Integrity, 2019)
A durability method in view of cathodic protection is proposed to improve the corrosion fatigue resistance of AH 32 steel in seawater. By aid of corrosion fatigue tests, the effects of thermal spraying Zn (zinc) and Cr (chromium) coating corrosion fatigue lives are quantitatively determined, respectively, and electrochemical measurement and fracture analysis are used to analyze the life-prolonging mechanism of these two coatings on corrosion fatigue. The results show that both Zn and Cr coating improve the corrosion fatigue resistance of AH 32 steel, and the effect enhances with the decrease of stress. The effect of Cr coating on corrosion fatigue of AH 32 steel mainly reflects in extending the crack initiation life for its better corrosion resistance. While the effect of Zn coating on corrosion fatigue lies in not only inhibiting the initiation of corrosion fatigue but also restraining crack propagation as cathodic protection materials. To sun up, Cr coating has a better durability effect than Zn coating at higher stress level, while Zn exceeds Cr at low stress level.
Keywords: Durability method; Corrosion fatigue; Thermal spraying; Crack nucleation; Crack propagation